Intereses convencionales, precio del dinero, tasas máximas y anatocismo: sobre el anteproyecto de reforma del Código Civil - Jiménez Jiménez, Eduardo Daniel (2021)
The author carries out a critical analysis from an economy and a legal perspective regarding the Draft Reform of the Civil Code, specifically on the chapter on interest payment, proposing some suggestions on the subject. Likewise, he suggests that it is necessary to study the nature of the interests linking the legal with the economic, in a multidisciplinary approach.